EFEKTIFITAS LAYANAN KONSELING KELOMPOK DALAM MENINGKATKAN KEDISIPLINAN SISWA DI MADRASAH ALIYAH NEGERI 1 MEDAN - Esti Cahya Ningsih; Siti Rahma Rambe; Eva Putri Sabrida Saragi; Arsyad Kamal; Ganda Rezeki Siregar; Annisa Arrumaisyah Daulay (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
The purpose of this study was to determine whether group counseling services improved the attitudes of MAN 1 MEDAN students toward discipline. This study uses a survey method. This study uses descriptive qualitative research. In qualitative research, researchers use data to answer questions or leave it up to interpretation. Careful observation, detailed contextual descriptions, extensive interview transcripts, and analysis of documents and records all contributed to data collection. The reconnaissance was directed at MAN 1 MEDAN located at Jalan William Iskandar No.7 B, Sidoarjo, Medan Tembun District, Medan City. The meeting will take place from Thursday to Saturday, October 20- 22, 2022 in the Orientation and Counseling Room (BK). At Madrasah Ariya Negri 1 Medan, I spoke with his counseling teacher and learned about his group counseling. This study aimed to determine the effectiveness of the MAN 1 MEDAN student group counseling service. MAN 1 MEDAN uses group counseling techniques to solve problems.